2012
DOI: 10.1002/jcc.23124
|View full text |Cite
|
Sign up to set email alerts
|

New basis sets for the evaluation of interaction‐induced electric properties in hydrogen‐bonded complexes

Abstract: Interaction-induced static electric properties, that is, dipole moment, polarizability, and first hyperpolarizability, of the CO-(HF)(n) and N(2)-(HF)(n), n = 1-9 hydrogen-bonded complexes are evaluated within the finite field approach using the Hartree-Fock, density functional theory, Møller-Plesset second-order perturbation theory, and coupled cluster methods, and the LPol-n (n = ds, dl, fs, fl) basis sets. To compare the performance of the different methods with respect to the increase of the complex size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…VP-EDS calculations were carried out using a modified version of the GAMESS (US) program. 85,86 Baranowska et al performed the assessment of basis sets on the electronic excess properties [26][27][28]40,43,44 and suggested that the use of basis sets specifically tailored for such type of calculations (for the analysis of schemes for eliminating the basis set superposition error in calculations of the properties in question we refer to Refs 30,87,88). However, as demonstrated recently by some of the present authors, property-oriented basis sets are not always the best choice to predict the nuclear relaxation (hyper)polarizabilities.…”
Section: Software and Computational Detailsmentioning
confidence: 99%
“…VP-EDS calculations were carried out using a modified version of the GAMESS (US) program. 85,86 Baranowska et al performed the assessment of basis sets on the electronic excess properties [26][27][28]40,43,44 and suggested that the use of basis sets specifically tailored for such type of calculations (for the analysis of schemes for eliminating the basis set superposition error in calculations of the properties in question we refer to Refs 30,87,88). However, as demonstrated recently by some of the present authors, property-oriented basis sets are not always the best choice to predict the nuclear relaxation (hyper)polarizabilities.…”
Section: Software and Computational Detailsmentioning
confidence: 99%
“…In the case of resonant NLO properties of molecules, like two-photon absorption, the treatment of vibrational contributions using DFT may lead to catastrophic predictions of vibrationally resolved spectra. , Let us recall that the nonresonant vibrational contributions to hyperpolarizability were in many cases found to be of the same magnitude or even larger than their electronic counterparts. As a natural step toward more complex systems, the electronic NLO properties of various types of weakly bound systems including hydrogen-bonded and van der Waals complexes were intensively studied by high-level post-Hartree–Fock ab initio as well as DFT methods. ,, It was found that the properties of hydrogen bonded systems can be satisfactorily described by LC-DFAs and also by some global hybrids (e.g., M06-2X) . In the case of van der Waals systems, these methods also performed well provided that the geometries used in the property calculations were optimized taking into account the dispersion interaction. , The good performance of LC-DFAs could be traced back not only to an improved description of the NLO properties of the individual subsystems but also to a better description of the interaction-induced ( excess ) component of NLO properties involving the effects of intermolecular interactions in the complex …”
Section: Introductionmentioning
confidence: 99%
“…Despite the small size, already the LPol‐ds basis set—the smallest among the LPol‐n sets—gives electric property results very close to those yielded by traditional basis sets of larger size, thus enabling accurate calculations for systems larger than previously. Excellent performance of the LPol‐n sets is reported for linear and nonlinear electric properties of isolated systems, as well as interaction‐induced electric properties in hydrogen‐bonded systems and van der Waals complexes …”
Section: Introductionmentioning
confidence: 99%